2020
DOI: 10.3390/condmat5020038
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Spectral Imaging by A THz-FEL

Abstract: Using the unique characteristics of the free-electron-laser (FEL), we successfully performed high-sensitivity spectral imaging of different materials in the terahertz (THz) and far-infrared (FIR) domain. THz imaging at various wavelengths was achieved using in situ spectroscopy by means of this wavelength tunable and monochromatic source. In particular, owing to its large intensity and directionality, we could collect high-sensitivity transmission imaging of extremely low-transparency materials and three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…THz imaging is one of the many challenging and stimulating THz applications. Using the unique characteristics of the FEL, Irizawa et al [38] successfully performed highsensitivity spectral imaging of different materials in the THz and far-infrared (FIR) domain. Due to the intensity and directionality of the ISIR source at Osaka, they collected high-sensitivity transmission imaging of extremely low-transparency materials and threedimensional objects in the 3-6 THz range.…”
Section: Discussionmentioning
confidence: 99%
“…THz imaging is one of the many challenging and stimulating THz applications. Using the unique characteristics of the FEL, Irizawa et al [38] successfully performed highsensitivity spectral imaging of different materials in the THz and far-infrared (FIR) domain. Due to the intensity and directionality of the ISIR source at Osaka, they collected high-sensitivity transmission imaging of extremely low-transparency materials and threedimensional objects in the 3-6 THz range.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging this advantage, along with the properties of MIR and THz radiation, it can be applied across various fields and applications. Consequently, MIR and THz FELs have found utility in numerous scientific research, industrial, and medical applications, including spectroscopy and imaging [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, IR-FELs are open at many synchrotron-radiation facilities all over the world since the optical emission was first observed at a laboratory level more than 50 years ago [ 31 ]. Various original experimental studies using IR-FELs are reported as follows: ablation of biological tissues [ 32 , 33 , 34 ], alteration of biological functions [ 35 , 36 ], degradation of protein–metal complexes [ 37 , 38 ], optical and spectroscopic imaging [ 39 , 40 , 41 ], structural dynamics of biomolecules [ 42 , 43 ], chemical reactions in the gas phase [ 44 , 45 , 46 ], decomposition of biopolymers [ 47 , 48 , 49 ], nonlinear-optical physics [ 50 ], and observation of terahertz radiation [ 51 ].…”
Section: Introductionmentioning
confidence: 99%